Efforts to Improve Students' Creativity and Learning Outcomes through the Demonstration Method in Creative Dance Using Property at Grade IX G SMP Negeri 2 Pulau Punjung - Darvita, Eni (The Future of Education Journal, 2022)
This research is attracted by the essence of learning Cultural Arts, namely to provide knowledge to students how they interact with their environment. These interactions creativity arises as a form of personality formation, skills, and intellectual development of students. Learning Arts and Culture also plays an important role in the education of insight, skills, and attitudes from an early age for students. However, in the process of teaching and learning Arts and Culture, what is expected is not in accordance with reality. The author uses the classroom action research conducted by the teacher in their own class by designing, implementing, and reflecting on actions in a participatory manner with the aim of improving the learning process in the classroom so that student activities and learning outcomes can increase. The research was conducted in class IX G of SMP Negeri 2 Pulau Punjung on the subject of Cultural Arts with the material "Arranging Creative Dance using property" in the odd semester of the 2018/2019 academic year. The number of students in class IX G is 24 people, consisting of 8 boys and 16 girls. The data collection tool used is observation: to collect data about the creativity of students in the teaching and learning process through an observation format. Test: used to obtain data about student learning outcomes through exam questions or tests. The data collected in each observation activity from the implementation of the CAR cycle was analyzed descriptively by using the percentage technique to see trends that occur in learning. The results of this study indicate that the use of the demonstration method can increase the creativity of class IX G students.